Remote service to solve the two-dimensional cutting stock problem: an application to the Canary Islands costume. (1st December 2008) - de Armas, Jesica; Leon, Coromoto; Miranda, Gara; Segura, Carlos
This paper presents the Graphical User Interface (GUI) for a remote service used to solve the two-dimensional guillotine cutting stock problem as applied to the textile industry. This interface allows for the patterns in the regional woman's dress of the city of La Orotava, in the Canary Islands, to be defined and manipulated. The user must choose the garment, its quantity and its sizes, as well as, the amount of material available. This information is then used by the system to arrange the patterns. Individual patterns may also be selected. Internally, the system implements a variant of the Viswanathan-Bagchi algorithm to solve the two-dimensional cutting stock problem. The solution is calculated remotely in a dedicated server. The user may, however, keep track of all those possibilities that were rejected by the algorithm in its search for the final solution. He/She can also modify the final solution by dragging the patterns with the mouse into the desired position on the surface. The GUI and the remote service were implemented using Java, while the solving algorithm was coded using C/C++.